Identification and characterization of a novel AA9-type lytic polysaccharide monooxygenase from a bagasse metagenome - Bunterngsook, Benjarat; Mhuantong, Wuttichai; Kanokratana, Pattanop; Iseki, Yu; Watanabe, Takashi; Champreda, Verawat (Applied Microbiology and Biotechnology, 2021)
Lytic polysaccharide monooxygenases (LPMOs) are auxiliary enzymes catalyzing oxidative cleavages of cellulose chains in crystalline regions, resulting in their increasing accessibility to the hydrolytic enzyme counterparts and hence higher released sugars from biomass saccharification. In this study, a novel auxiliary protein family 9 LPMO (BgAA9) was identified from a metagenomic library derived from a thermophilic microbial community in bagasse collection site where diverse AA9 and AA10 putative sequences were annotated. The enzyme showed highest similarity to a glycoside hydrolase family 61 from Chaetomium thermophilum . Recombinant BgAA9 expressed in Pichia pastoris cleaved cellohexaose (DP6) into shorter cellooligosaccharides (DP2, DP3, and DP4). Supplementation BgAA9 to a commercial cellulase, Accellerase® 1500 showed strong synergistic effect on saccharification of Avicel® PH101, decrystallized cellulose, filter paper, and alkaline-pretreated sugarcane bagasse, resulting in 63–93% increase in the total reducing sugar yield after incubation at 50 °C for 72 h. Strong synergism was shown between BgAA9 and the cellulase with the highest total fermentable sugar yield obtained from 75:25% of Accellerase®1500:BgAA9 which released 39 mg glucose/FPU (filter paper unit) equivalent to 38.7% higher than Accellerase®1500 alone at the same total protein dosage of 5 mg/g substrate according to the mixture design study. The enzyme represented the first characterized LPMO from environmental metagenome and a potent auxiliary component for biomass saccharification. Key points • BgAA9 represents the first characterized LPMO from metagenome. • 12 AA families were annotated in thermophilic bagasse fosmid library by NGS. • BgAA9 showed homology to Cel61 in Chaetomium thermophilum. • BgAA9 oxidized cellohexaose and PASC to DP2, DP4, and DP6. • BgAA9 showed strong synergism to Accellerase on bagasse hydrolysis.